FERMI-LAT STUDY OF GAMMA-RAY EMISSION IN THE DIRECTION OF SUPERNOVA REMNANT W49B - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2010)
We present an analysis of the gamma-ray data obtained with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope in the direction of SNR W49B (G43.3-0.2). A bright unresolved gamma-ray source detected at a significance of 38 sigma is found to coincide with SNR W49B. The energy spectrum in the 0.2-200 GeV range gradually steepens toward high energies. The luminosity is estimated to be 1.5 x 10(36) (D/8 kpc)(2) erg s(-1) in this energy range. There is no indication that the gamma-ray emission comes from a pulsar. Assuming that the supernova remnant (SNR) shell is the site of gamma-ray production, the observed spectrum can be explained either by the decay of neutral pi mesons produced through the proton-proton collisions or by electron bremsstrahlung. The calculated energy density of relativistic particles responsible for the LAT flux is estimated to be remarkably large, U-e,U-p > 10(4) eV cm(-3), for either gamma-ray production mechanism.
CRIS-Team WoS Importer:2020-01-15